2008
DOI: 10.1128/jvi.01957-07
|View full text |Cite
|
Sign up to set email alerts
|

The Picornavirus Avian Encephalomyelitis Virus Possesses a Hepatitis C Virus-Like Internal Ribosome Entry Site Element

Abstract: Avian encephalomyelitis virus (AEV) is a picornavirus that causes disease in poultry worldwide, and flocks must be vaccinated for protection. AEV is currently classified within the hepatovirus genus, since its proteins are most closely related to those of hepatitis A virus (HAV). We now provide evidence that the 494-nucleotidelong 5 untranslated region of the AEV genome contains an internal ribosome entry site (IRES) element that functions efficiently in vitro and in mammalian cells. Unlike the HAV IRES, the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 37 publications
4
55
0
Order By: Relevance
“…The requirements for 48S complex formation on the simian picornavirus SPV9 IRES were similar to those for PTV-1 IRES, but in contrast to HCV IRES, eIF4F and eIF4B stimulated the formation of 48S complexes (de Breyne et al, 2008b). It is interesting to note that the AEV IRES, like the SPV9 IRES, showed partial requirement for eIF4F components (Bakhshesh et al, 2008). These results suggest mechanistic differences with the HCV IRES that need to be analyzed in further studies.…”
Section: Picornavirus Ires Elements Diversitymentioning
confidence: 65%
See 1 more Smart Citation
“…The requirements for 48S complex formation on the simian picornavirus SPV9 IRES were similar to those for PTV-1 IRES, but in contrast to HCV IRES, eIF4F and eIF4B stimulated the formation of 48S complexes (de Breyne et al, 2008b). It is interesting to note that the AEV IRES, like the SPV9 IRES, showed partial requirement for eIF4F components (Bakhshesh et al, 2008). These results suggest mechanistic differences with the HCV IRES that need to be analyzed in further studies.…”
Section: Picornavirus Ires Elements Diversitymentioning
confidence: 65%
“…These elements are cis-acting RNA regulatory sequences endowed with the capacity to govern cap-independent translation initiation in mRNAs that are translated when cap-dependent translation is compromised. Subsequent studies demonstrated that IRES elements drive internal initiation of translation in the RNA of all members of the Picornaviridae family (Bakhshesh et al, 2008;Borman and Jackson, 1992;Brown et al, 1991;Hinton and Crabb, 2001;Hinton et al, 2000;Kaku et al, 2002;Kuhn et al, 1990;Nateri et al, 2000;Sweeney et al, 2012;Willcocks et al, 2011;Yu et al, 2011b). The genome of other RNA viruses also contains IRES elements, as illustrated by hepacivirus, pestivirus, dicistrovirus, retrovirus Tsukiyama-Kohara et al, 1992;Vallejos et al, 2010;Wilson et al, 2000), as well as some RNA viruses infecting plants and protozoa (reviewed in Martinez-Salas et al, 2012).…”
Section: Features Of the Picornavirus Untranslated Regionmentioning
confidence: 99%
“…), and a seal picornavirus (Kapoor et al 2008), also contain this class of IRES element (see Hellen and de Breyne 2007). A distinctive feature of this class of IRES elements is their resistance to the action of hippuristanol (Bordeleau et al 2006;Chard et al 2006b;Bakhshesh et al 2008), a specific inhibitor of eIF4A, which is consistent with their lack of requirement for any eIF4 initiation factors for 48S initiation complex assembly in vitro (Pestova et al 1998;Pisarev et al 2004).…”
Section: Introductionmentioning
confidence: 79%
“…The cap dependence of these transcripts is readily demonstrated by the coexpression of an enterovirus 2A protease, which induces the cleavage of eIF4G and inhibits cap-dependent protein synthesis. In the following experiments, we have used the plasmid pGEM3Z/J1, which expresses the 1D-2A region of the swine vesicular disease virus (SVDV) polyprotein, for this purpose as described previously (Sakoda et al 2001;Chard et al 2006a;Bakhshesh et al 2008). Derivatives of the pRBRluc vector were produced containing the wildtype and defective forms of the EMCV IRES (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation